D3‐creatine dilution, computed tomography and dual‐energy X‐ray absorptiometry for assessing myopenia and physical function in colon cancer: A cross‐sectional study - En Cheng; Bette J. Caan; Peggy M. Cawthon; William J. Evans; Marc K. Hellerstein; Mahalakshmi Shankaran; Kristin L. Campbell; Alexandra M. Binder; Barbara Sternfeld; Jeffrey A. Meyerhardt; Kathryn H. Schmitz; Elizabeth M. Cespedes Feliciano (Wiley, 2023)
Abstract Background Low skeletal muscle mass (myopenia) is common in cancer populations and is associated with functional decline and mortality, but prior oncology studies did not assess total body skeletal muscle mass. Instead, they measured surrogates such as cross‐sectional area (CSA) of skeletal muscle at L3 from computed tomography (CT) or appendicular lean mass (ALM) from dual‐energy X‐ray absorptiometry (DXA). D3‐creatine (D3Cr) dilution is a non‐invasive method to assess total body skeletal muscle mass, which has been examined in a variety of populations but not in cancer. To compare the associations of D3Cr muscle mass, CT CSA, and DXA ALM with myopenia and physical function, we conducted a cross‐sectional study among 119 patients with colon cancer (2018-2022). Methods For each technique (D3Cr, CT and DXA), myopenia was defined as the lowest sex‐specific quartile of its measurement. Physical function was measured by the short physical performance battery and grip strength. We calculated Pearson correlations (r) among three techniques, computed Cohen's kappa coefficients (κ) to assess the agreement of myopenia, and estimated Pearson correlations (r) of three techniques with physical function. All analyses were sex‐specific. Results Sixty‐one (51.3%) participants were male, the mean (standard deviation) age was 56.6 (12.9) years, and most (68.9%) had high physical function (short physical performance battery: ≥11 points). Correlations and myopenia agreement among three techniques were greater in men than women; for example, regarding D3Cr muscle mass versus CT CSA, r was 0.73 (P < 0.001) for men versus 0.45 (P < 0.001) for women, and κ was 0.82 (95% CI: 0.65, 0.99) for men versus 0.24 (95% CI: −0.08, 0.52) for women. Among men, higher D3Cr muscle mass was significantly correlated with faster gait speed (r = 0.43, P < 0.01) and stronger grip strength (r = 0.32, P < 0.05); similar correlations were observed for CT CSA and DXA ALM. However, among women, no measure of muscle or lean mass was significantly associated with physical function. Conclusions This is the first study using D3‐creatine dilution method to assess muscle mass in a cancer population. Regardless of the techniques used for muscle or lean mass assessment, we observed stronger correlations, greater myopenia agreement, and more significant associations with physical function in men with colon cancer than women. D3Cr, CT and DXA are not interchangeable methods for assessing myopenia and physical function, especially in women with colon cancer. Future studies should consider relative advantages of these techniques and examine the D3‐creatine dilution method in other cancer types.